Combinations of Pakcoy (Brassica Rapa L) Juice and Anti Hypertension Drugs for Lowering Blood Pressure in Hypertension Pregnant Women in Handil Baru Health Center Year 2023 - Ulfa Siti Mardiyah; Nina Mardiana; Damai Noviasari; Ernani Setyawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Handil Baru Health Center had cases of hypertension in 2021 as many as 27 cases of pregnant women and 1 case of maternal death and 40 LBW babies was found, one of the causes of preterm parturition was due to mothers experiencing preeclampsia or eclampsia. So far, midwives have tried to reduce cases of hypertension through counseling. To determine the effect of a combination of Pakcoy (Brassica rapa L) juice and anti-hypertensive drugs on reducing blood pressure in hypertensive pregnant women at the Handil Baru Health Center. This type of research is quasi-experimental, with a One Group Pre-Test – Post-Test Design without a Control Group. The population is all hypertensive pregnant women at the Handil Baru Health Center in January-July 2023 totaling 14 people. The sampling technique in this study is total sampling, so that the sample fits the population. data using independent t test. Results: There is an effect of hypertension medication and Pakcoy (Brassica rapa L) juice on blood pressure (p value 0.000 <α: 0.05). Support for hypertension medication can be given Pakcoy juice, because Pakcoy which contains potassium, calcium and magnesium can help lower blood pressure naturally. Consuming 4,700 milligrams of potassium daily can lower blood pressure caused by high sodium intake. There is a combination effect of giving Pakcoy juice (Brassica rapa L) and anti-hypertensive drugs on blood pressure in hypertensive pregnant women at the Handil Baru Health Center about 19%. Handil Baru Health Center is expected to socialize health education about preventing hypertensive pregnant women